2017
DOI: 10.1002/acr.23225
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Rheumatoid Arthritis Symptoms: Survey Results From a Rheumatoid Arthritis Registry

Abstract: Objective Patients with RA often ask if specific foods, popularized as “inflammatory” or “anti-inflammatory,” can improve or worsen their RA. We surveyed patients regarding diet and RA symptoms. Methods We mailed a diet survey to 300 subjects in a single-center RA registry at a large academic center. Subjects were asked whether they consume each of 20 foods and whether these foods make their RA symptoms better, worse, or unchanged. Semi-annual registry data include demographics, medications, comorbidities, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 13 publications
2
62
0
4
Order By: Relevance
“…The patients with RA also reported a lower intake of discretionary foods compared to the general population. This was in line with previous data, indicating that patients with RA report that these foods worsen their symptoms [ 28 ] and they therefore might avoid them. Additionally, the patients with RA had all volunteered to participate in a dietary intervention trial, and might therefore have been more interested in diet than the general population.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The patients with RA also reported a lower intake of discretionary foods compared to the general population. This was in line with previous data, indicating that patients with RA report that these foods worsen their symptoms [ 28 ] and they therefore might avoid them. Additionally, the patients with RA had all volunteered to participate in a dietary intervention trial, and might therefore have been more interested in diet than the general population.…”
Section: Discussionsupporting
confidence: 93%
“…Possibly, a higher intake of dietary fiber (plant-based foods such as fruit and vegetables and whole grain) and a high-quality fat intake (lower intake of saturated fats and a higher intake of unsaturated and long-chain polyunsaturated fatty acids) could contribute to decreased inflammation and disease activity. However, despite indications from patients with RA that dietary intake impacts the disease [ 28 ], there is a great lack of research in this area.…”
Section: Introductionmentioning
confidence: 99%
“…A small cross-sectional case series of 53 women with RA indicated that the patients overall had a low dietary consumption of vitamins A and C, and zinc, and in the elderly in particular there was low consumption of vitamin E and selenium ( Silva et al, 2014 ). In a survey study of a single-center RA registry, 24% of subjects reported that foods affect their RA, with 15% reporting improvement and 19% worsening ( Tedeschi et al, 2017 ). Blueberries and spinach were the foods most often reported to improve RA symptoms, while soda with sugar and desserts were most often reported to worsen RA symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey, 24% of patients reported perceived effects of their diet on RA symptoms; 19% observed negative effects of sugary drinks and sweets, while 15% reported beneficial effects of some foods’ consumption, most often berries or spinach [ 23 ]. It might be worthwhile to try to provide some insight through clinical studies of whether perceptions match reality.…”
Section: Other Dietary Factors Potentially Lowering Rheumatoid Arthrimentioning
confidence: 99%